AN ASSESSMENT OF CLIMATIC VARIATIONS AND IMPLICATIONS ON CROP YIELDS IN KATSINA STATE, NIGERIA - Adeniyi, A.; Yahaya, O. Y. (FUDMA JOURNAL OF SCIENCES, 2023)
The implications of climate variations are many and varied as it influences drought, rainfall pattern and agricultural productivity in a negative manner especially in northern Nigeria. Climate variability impacts on agricultural yields and livelihood is becoming increasingly adverse over time and potentially catastrophic especially in some areas of northern Nigeria. This study basically focuses on the assessment of climatic variations and the implication on crop yields in Katsina State. The study used climatic data (temperature and rainfall) and data on crop yields (millet, sorghum, cowpea, rice and maize). Climatic data on temperature and rainfall were collected for the period of twelve years (2004-2015). Similarly, crop yields data on millet, sorghum, cowpea, rice and maize were also collected for the same period. Descriptive statistics- mean, standard deviation and coefficient of variation were employed in data analysis. Multiple regression and trend analysis were also employed. The result of the analysis reveals that data on crop yield varies from one year to the other. Millet, rice and maize yields exhibits downward trend while cowpea exhibits upward trend. Similarly, the result of the analysis of the relationship between climatic parameters and the crop yields shows that temperature and rainfall have a weak relationship on the variations in the selected crop yields. The outcome of the result shows that variations in the yield of the selected crops could be credited to other factors outside the selected climatic elements. The paper therefore, suggests the adoption of modern farming system, application of fertilizer, soil and water conservation
Keywords: Assessment, Climatic Variation, Trend and Crop yield